Atypical presentation of herpes simplex virus type 1 infection in paediatric burns patients in a large tertiary hospital, South Africa - Mpho L. Sikhosana; Asma Salloo; Monica Birkhead; Kerrigan McCarthy (AOSIS, 2019)
Introduction: Herpes simplex virus has been reported in the literature to commonly complicate burn wounds. However, there is paucity of such data in the South African setting. Case presentation: Eight paediatric burns patients with ages ranging between 10 months and 5 years presented with a febrile maculopapular rash illness in a paediatric ward of a large South African tertiary hospital. The rash became vesicular in three cases, involving the limbs and face. Varicella was suspected. Management and outcome: Medical records of suspected cases were reviewed. Blood, vesicular fluid and scab samples were collected. Electron microscopy of vesicular fluid revealed herpes virus particles. Laboratory testing confirmed herpes simplex virus type 1. Conclusion: Herpes simplex virus type 1 infection can present atypically in burns patients.